Contents of the Institutional Perspective Curriculum - Jajang Rustandi; Abdurrahmansyah (Formosa Journal of Science and Technology, 2022)
Curriculum is a set of subjects and educational programs provided by an educational institution that contains lesson plans to be given to lesson participants in one period of education level. Institutional goals are the goals to be achieved by an educational institution as an education provider. Institutional goals are intermediate goals to achieve general goals that are formulated, in the form of competence of graduates at each level of education, basic education, secondary education, vocational, and higher education. Subjects compiled or presented in each primary and secondary education unit (SD/ MI/ MTS/ SMP/ SMA/ MA) are grouped into several main subjects namely, natural sciences, social sciences, arts and culture, physical education and sport. body, and local content. Each of the subjects mentioned above, of course, has its own characteristics and goals and is different from the goals to be achieved by other subjects. Subject objectives are the elaboration of curriculum objectives in order to achieve national education goals.